Multisurface plasticity models under yielding conditions/Multisurface-plastizitäts-modelle mit zusammengesetzten fliessbedingungen - Hintze, Dagmar; Will, Johannes (Journal of Civil Engineering and Management, 1999)
An implicit integration algorithm for arbitrary multi- surface plasticity is presented. This perfectly-plastic model uses isotrop and anisotrop Mohr-Coulomb criteria with tension-cutoff and associated or non-associated flow rules. So materials with anisotropic deformation and strength behaviour like intact rock with sets of joints can be described. With an extended Drucker-Prager-criterion for the isotrop material matrix this model can be used as well for modelling other materials such as masonry or concrete. Problems resulting from arbitrary multisurface yield criteria are discussed. Consistent numerical algorithms for robust numerical solutions are presented. The Multisurface plasticity model was implemented in a finite-element-program. The example of calculation of a dam on jointed rock mass shows the applicability and new possibilities for the description of anisotropic materials.Daugiapaviršiai plastiškumo modeliai takumo sąlygomisSantrauka. Pateikiamas algoritmas pasirinktiems daugiapaviršiams plastiškumo modeliams. Visiško plastiškumo modelyje taikomi izotropinis ir anizotropinis Mohr-Coulomb kriterijai tempimoištiesintais ir asocijuoto arba neasocijuoto tekėjimo sąlygomis. Pagai tokį modelį gali būti aprašytos medžiagos, kurioms būdinga anizotropinė deformacija ir stiprumo pokyčiai, taip kaip ir nejudinta uoliena su jungčių tinklu. Taikant išplėstinį Drucker-Prager kriterijų izotropinės medžiagos matricai šis modelis taip pat gali būti taikomas ir kitoms medžiagoms modeliuoti, pvz., mūrui ar betonui. Aptariami uždaviniai gauti iš pasirinktų daugiapavirši[udot] takumo kriterijų. Daugiapaviršis plastiškumo modelis buvo įvestas į baigtinių elementų programą. Užtvankos iš uolienos su margais skaičiavimas iliustruoja tinkamumą ir naujas galimybes aprašyti anizotropines medžiagas.Article in German.First Published Online: 26 Jul 2012